Positive effects of online games on the growth of college students: A qualitative study from China - Li, Feiyue; Zhang, Di; Wu, Suowei; Zhou, Rui; Dong, Chaoqun; Zhang, Jingjing (Frontiers in Psychology, 2023)
Objectives This study aimed to explore the positive effects of online games on college students’ psychological demands and individual growth. Methods A qualitative study design was carried out in September 2021. Semi-structured, in-depth, and individual interviews were conducted with a purposive sample of 20 undergraduates who played the online game “Glory of Kings” from six universities. Thematic analysis was employed to explore the positive features caused by “Glory of Kings”. Results College students reported three positive effects of online games, namely, satisfying the need for personal growth, meeting the requirement of social life and promoting academic performance. Conclusion College educators and families should take advantage of the positive effect of online games to guide college students to use online games reasonably.